2007
DOI: 10.1002/art.22923
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers predict radiographic progression in early rheumatoid arthritis and perform well compared with traditional markers

Abstract: Objective. To evaluate the performance of biochemical and traditional markers in predicting radiographic progression in rheumatoid arthritis (RA).Methods. One hundred thirty-two patients with early RA were treated with nonbiologic therapies for 2 years and studied longitudinally. Genomic DNA was analyzed for presence of the shared epitope. Conclusion. These results indicate that biochemical markers are useful predictors of radiographic progression in RA and that serum MMP-3 levels decrease significantly with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 49 publications
11
70
3
2
Order By: Relevance
“…1C), accompanied by an increase in serum MMP-3 ( Fig. 1D), a marker used to diagnose arthritis (13), indicating that the loss of Author contributions: K.K., S.S., and S.N. designed research; K.K., H.T., Y.K., and S.S. performed research; K.K., H.T., Y.K., S.S., and S.N.…”
Section: Deletion Of the Dnase II Gene In Bone Marrow-derived Cells Cmentioning
confidence: 99%
“…1C), accompanied by an increase in serum MMP-3 ( Fig. 1D), a marker used to diagnose arthritis (13), indicating that the loss of Author contributions: K.K., S.S., and S.N. designed research; K.K., H.T., Y.K., and S.S. performed research; K.K., H.T., Y.K., S.S., and S.N.…”
Section: Deletion Of the Dnase II Gene In Bone Marrow-derived Cells Cmentioning
confidence: 99%
“…The correlation of these parameters in patients demonstrating low values of traditional prognostic markers including ESR, CRP, RF and DAS was greatly reported (Månsson et al, 1999;Skoumal et al, 2004). Additionally, COMP may be of prognostic value for radiological outcome and proposed its feasibility in monitoring articular cartilage damage in RA (Skoumal et al, 2003;Young-Min et al, 2007;Morozzi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…By multivariate analysis, a model including MMP-3 and CTX-II was identified as providing the best prediction of radiographic progression at baseline and a combination of MMP-3, CTX-II, and swollen joint count formed the best longitudinal AUC model. 66 In another experiment involving patients with RA and systemic lupus erythematosus (SLE), it was found that levels of MMP-2 and MMP-9 were higher than controls in both groups of patients, supporting the involvement of MMP proteins in these autoimmune disorders. 67 Baseline serum levels of 2 elements of the metalloproteinase network, MMP-1 and TIMP-1, reflected subsequent joint destruction.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 96%
“…116 The serum levels of CRP not only reflect the extent of disease activity but are also associated with joint destruction. 66,121 In an inception cohort of patients with early inflammatory polyarthritis followed prospectively for outcome, CRP was found to be the best predictor of radiographic damage by five years. 122 In addition, CRP determination is widely available, easy to perform and of low cost, making it the preferred biomarker of disease activity.…”
Section: C-reactive Proteinmentioning
confidence: 99%